Peningkatan Keterampilan Menceritakan Kembali Cerita Fabel melalui Teknik Paired Storytelling pada Siswa Sekolah Dasar - Salam; Munirah (Pedagogical Education and Review of Linguistics, 2025)
This study aims to improve the retelling skills of fable stories among fifth-grade students through the implementation of the paired storytelling technique and hand puppet media. The method used is Classroom Action Research (CAR), involving 20 fifth-grade students in the 2022/2023 academic year. The study was conducted in two cycles, with each cycle consisting of two meetings. Data were collected through observation and performance tests, then analyzed using quantitative and qualitative descriptive analysis. The results showed that only 9 students were able to effectively retell the fable stories they heard or read according to the competencies, while the other 11 students required guidance. The application of paired storytelling techniques and the use of hand puppet media proved effective in improving the retelling skills of most students.